Effect of Applying Force to Self‐Adhesive Electrodes on Transthoracic Impedance: Implications for Electrical Cardioversion. Issue 10 (22nd September 2016) - RAMIREZ, F. DANIEL; FISET, SANDRA L.; CLELAND, MARK J.; ZAKUTNEY, TIMOTHY J.; NERY, PABLO B.; NAIR, GIRISH M.; REDPATH, CALUM J.; SADEK, MOUHANNAD M.; BIRNIE, DAVID H.
Abstract : Background: Current guidelines disagree on the role for applying force to electrodes during electrical cardioversion (ECV) for atrial fibrillation, particularly when using self‐adhesive pads. We evaluated the impact of this practice on transthoracic impedance (TTI) with varying force and in individuals with differing body mass indices (BMI). We additionally assessed whether specific prompts could improve physicians' ECV technique. Methods: The study comprised three parts: (1) TTI was measured in 11 participants throughout the respiratory cycle and with variable force applied to self‐adhesive electrodes in anteroposterior (AP) and anterolateral (AL) configurations. (2) Three participants in different BMI classes then had TTI measured with prespecified incremental force applied. (3) Ten blinded cardiology trainees simulated ECV on one participant with and without prompting (guideline reminders and force analogies) while force applied and TTI were measured. Results: The AP approach was associated with 13% lower TTI than AL (P < 0.001). Strongly negative correlations were observed between force applied and TTI in the AL position, irrespective of BMI (P ≤ 0.003). In all cases, 80% of the total reduction in TTI observed was achieved with 8 kg‐force (∼80 N). All prompts resulted in significantly greater force applied and modest reductions in TTI. Conclusions: Applying force to self‐adhesive electrodes reduces TTI and should be considered as a means of improving ECV success. Numerically greater mean force applied with a "push‐up" force analogy suggests that "concrete" cues may be useful in improving ECV technique.